Schwannoma of floor of mouth: A case report - Anjum Farooqui; Yogita Khalekar; Jamebaseer Farooqui; Vikrant Kasat (Wolters Kluwer Medknow Publications, 2017)
Schwannoma (neurilemmoma) is a benign nerve sheath tumor that is composed entirely of well-differentiated Schwann cells. It is important to highlight that schwannoma is usually found in the head and neck and rarely in the oral cavity. Schwannoma is a benign tumor that originates from the Schwann cells of the peripheral nerves. They are usually asymptomatic, do not recur, and malignant transformation is rare. Here, we report a case of neurilemmoma that was located at an unusual location, i.e., floor of the mouth.